VD_FINDINFO Jug / 2012 / 64 vom 22. November 2011 - VD Tribunal cantonal (2011)
TENTATIVEDROIT PÉNAL, CONTRAINTE SEXUELLE, ACTE D'ORDRE SEXUEL AVEC UN ENFANT, VIOL | 181 CP, 187 ch. 1 CP, 189 al. 1 CP, 190 CP, 22 al. 1 CP